Infections during Induction Chemotherapy in Children with Acute Lymphoblastic Leukemia – Profile and Outcomes: Experience from a Cancer Center in South India - Rajeswari, Binitha; Sukumaran Nair, Reghu K; Guruprasad, C S; Nair, Manjusha; Thankamony, Priyakumari; Parukutty, Kusumakumary (Indian Journal of Medical and Paediatric Oncology, 2018)
Objective:The objective of this study is to describe the incidence, clinical, laboratory and microbiological profile, treatment, and outcome of infections during induction chemotherapy in children with acute lymphoblastic leukemia (ALL). Materials and Methods: This was prospective, observational study. All children aged 1–14 years, newly diagnosed to have ALL and attending the Pediatric oncology division at our center were included. Induction chemotherapy was administered as per a modified Berlin-Frankfurt-Münster protocol. The study period was from January 2014 to June 2015. Results: Two hundred and twenty-seven patients with ALL were included in the study. One hundred and fifty episodes of infection occurred among 117 patients. Major sites of infection were lung (n = 35) and gastrointestinal tract (n = 30). Blood cultures were positive in 45 episodes (30.6%) with Gram negative organisms being the predominant isolates. The most common organisms isolated were Pseudomonas aeruginosa and Klebsiella spp. The response to antibiotics was good with only 18% of episodes requiring a third-line antibiotic. One hundred and thirty-six (90.6%) episodes resolved without sequelae. Overall induction mortality (12 out of 227-5.3%) was mainly accounted for by infections. Conclusions: Infections are the major cause of mortality and morbidity in patients with ALL on induction chemotherapy. The outcomes are good for the majority of patients if they receive adequate antibiotics early in the course of infection.
Keywords: Acute lymphoblastic leukemia; induction chemotherapy; infections